The Dynamics of Price Competition from Islamic Economic Perspective - Wicaksono, Rianto Anugerah (Jurnal Ekonomika dan Bisnis Islam, 2025)
The rapid growth of Indonesia's e-commerce sector has triggered market saturation, driven by increasing sellers, technological advancements, and consumer price sensitivity. This study aims to analyze the dynamics of market saturation and price competition, focusing on their implications for sellers and consumers. Employing a qualitative approach, the research integrates thematic analysis and causal-loop diagrams to uncover the relationships between market forces and their effects. Findings reveal that low entry barriers and high price transparency intensify price competition, reducing profitability and driving unsustainable practices. Consumers, increasingly price-sensitive, prioritize affordability over quality, creating a negative feedback loop that exacerbates saturation. From an Islamic economic perspective, these dynamics violate the principles of justice (al-adl) and balance (al-mizan), emphasizing the need for ethical business practices and equitable competition. This research underscores the importance of innovative strategies and policy interventions to create a fairer and more sustainable e-commerce ecosystem aligned with Islamic principles.